2004
DOI: 10.1104/pp.104.051508
|View full text |Cite
|
Sign up to set email alerts
|

Untranslated Regions from C4 Amaranth AhRbcS1 mRNAs Confer Translational Enhancement and Preferential Bundle Sheath Cell Expression in Transgenic C4Flaveria bidentis

Abstract: Many aspects of photosynthetic gene expression are posttranscriptionally regulated in C4 plants. To determine if RbcS mRNA untranslated regions (UTRs) in themselves could confer any characteristic C4 expression patterns, 5′- and 3′-UTRs of AhRbcS1 mRNA from the C4 dicot amaranth were linked to a gusA reporter gene. These were constitutively transcribed from a cauliflower mosaic virus promoter and assayed for posttranscriptional expression patterns in transgenic lines of the C4 dicot Flaveria bidentis. Three ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 86 publications
1
36
2
Order By: Relevance
“…The evolution of C 4 photosynthesis from the C 3 ancestral state requires mechanisms generating increased abundance as well as cell specificity of a large number of enzymes (Marshall et al, 1997;Patel et al, 2004;Gowik et al, 2004;Wiludda et al, 2012). A recent study has suggested that the evolution of increased abundance can be complex, with multiple sequences within promoters and 59 UTRs contributing to the expression of C 4 genes (Wiludda et al, 2012).…”
Section: Discussion Evolutionary Events Underlying the Recruitment Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of C 4 photosynthesis from the C 3 ancestral state requires mechanisms generating increased abundance as well as cell specificity of a large number of enzymes (Marshall et al, 1997;Patel et al, 2004;Gowik et al, 2004;Wiludda et al, 2012). A recent study has suggested that the evolution of increased abundance can be complex, with multiple sequences within promoters and 59 UTRs contributing to the expression of C 4 genes (Wiludda et al, 2012).…”
Section: Discussion Evolutionary Events Underlying the Recruitment Ofmentioning
confidence: 99%
“…For example, the increased abundance of C 4 enzymes can be conferred by elements within the promoter (Matsuoka et al, 1994;Gowik et al, 2004;Kajala et al, 2012;Wiludda et al, 2012), intron (Nomura et al, 2005b), or untranslated regions (UTRs) (Ali and Taylor, 2001;Wiludda et al, 2012). Similarly, cell specificity can be generated by the promoter (Matsuoka et al, 1994;Gowik et al, 2004), exon , or UTRs (Patel et al, 2004;Kajala et al, 2012). As these studies focused on a number of genes isolated from phylogenetically distinct C 4 species, they suggest that the mechanisms regulating genes of the C 4 pathway vary both within and between independent C 4 lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco leaves were simultaneously inoculated with Fny-CMV and Fny-CMVD2b on opposite surfaces of the leaf or on adjacent areas on the same surface. At 3-4 weeks after inoculation these co-inoculation zones were excised from leaves and prepared for in situ hybridization by using a protocol adapted from previously published methods (Long & Berry, 1996;Patel et al, 2004;Ruzin, 1999;Wang et al, 1993). Tissue samples were fixed by vacuum infiltration in 1 % (v/v) glutaraldehyde in 0.05 M sodium cacodylate buffer and incubated overnight at 4 uC, then dehydrated through an ethanol/tert-butyl alcohol series and embedded in Paraplast Plus (Monoject Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the slides were dried and immediately used for pre-hybridization. Slides were incubated for 10 min in 26 SSC before pre-hybridization and hybridization at 50 uC, followed by washing in various dilutions of SSC as described previously (Long & Berry, 1996;Patel et al, 2004;Wang et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…In higher plants, RBCL is encoded by the chloroplastic rbcL gene, while RBCS is encoded by members of the nuclear rbcS gene family (Sasanuma, 2001;Wostrikoff and Stern, 2007). The expression of rbcL and rbcS is highly regulated and can be influenced by cell and tissue development (Patel et al, 2004;Majeran et al, 2005), photosynthetic metabolism (Acevedo-Hernández et al, 2005), nutrients, and plant regulators (Imai et al, 2005;Patel et al, 2006). Liu et al (2013) suggested that the rootstocks affect the regulation of photosynthesis in cucumber leaves, since they affect the initial and total Rubisco activity by influencing gene expression.…”
Section: Introductionmentioning
confidence: 99%